Gambaran Perilaku 5M Plus Masyarakat dalam Pencegahan Demam Berdarah Dengue - Febri Diana Putri, Ni Putu; Achjar, Komang Ayu Henny; Gama, I Ketut; Sudiantara, Ketut; Suardana, I Wayan (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2023)
Factor related to the incidence of dengue hemorrhagic fever or DHF include behavioural factors, which consist of knowledge, attitudes and actions. This study aims to show the Description of 5M Plus behavior of the community in preventing Dengue Hemorrhagic Fever in Gelgel Village, Klungkung Regency in 2022. The type of research used is descriptive. The population in this study was 90 people. The number of samples based on the inclusion and exclusion criteria used in this study were 47 people. The research was conducted in April 2022. Data collection using questionnaire method which includes knowledge, attitudes, and skills, each with 5 questions.The age level shows that most of them have an age of 18-25 yearsas many as 27 people (57.4%), women as a characteristic based on gender were 32 people (68.1%). There are 19 of students (40.4%), and education degree high school student as many as 43 people (91.5%). The description of the respondent's behavior based on the knowledge of the majority is good as many as 43 people (91.5%), attitudes of 30 people (63.8%), and skills of 19 people (40.4%). Based on the results of research that includes the behavior of preventing dengue with 5M plus the average is good. However, there is still something which not good enough, namely the skills of the community at the age of 18-25 years as many as 11 people (23.4%). The results of the study can be used as input to increase knowledge and reference about the description of community behaviour regarding 5M plus in the prevention of dengue hemorrhagic fever in Gelgel Village, Klungkung Regency in 2022.